The Impact of Proximity on Consumer Fair Trade Engagement and Purchasing Behavior: The Moderating Role of Empathic Concern and Hypocrisy - Gillani, Alvina; Kutaula, Smirti; Leonidou, Leonidas C.; Christodoulides, Paul (My University, 2021)
The article reports the findings of an empirical study among consumers, regarding the impact of physical, social, and psychological proximity on their engagement to the fair trade idea and purchasing behavior. Based on a random sample of 211 British and 112 Indian consumers and using structural equation modeling, it was found that high levels of physical, social, and psychological proximity leads to high consumer fair trade engagement. Moreover, consumer fair trade engagement was confirmed to have a positive impact on fair trade purchasing behavior. Furthermore, consumer empathic concern was found to positively moderate the association between proximity and consumer fair trade engagement, while the opposite was true with regard to consumer hypocrisy. Finally, consumer nationality was found to have a control effect on physical, social, and psychological proximity, with the latter felt stronger among Indian, as opposed to British consumers.
Keywords: Consumer engagement; Fair trade; Consumer proximity; Empathic concern; Hypocrisy